Upaya Pengembangan Layanan Melalui "Program SATU KECAMATAN SATU BUKU (SAKE SABUK)" di Perpustakaan Umum Kabupaten Sumedang - Auliah, Lia Fitri; Sukaesih, Sukaesih; Prahatmaja, Nurmaya (Jurnal Pustaka Ilmiah, 2022)
The development of services in the library can be implemented through certain programs that are related to the objectives to be achieved in the library, one of which is information services related to regional characteristics contained in the Satu Kecamatan Satu Buku (Sake Sabuk) Program. The purpose of this study was to describe and analyze the Sake Sabuk Program as an effort to develop services at the Sumedang District Public Library. The research method used is qualitative. Data were obtained through interviews, observation, documentation, and literature study. The research results obtained that the efforts made by the Sumedang District Public Library by implementing the Sake Sabuk Program had a good impact on service development activities in the library. The community becomes aware of the uniqueness of the Sumedang Regency area. In its implementation, this program received various support from both internal and external parties. In addition, the implementation of the program is inseparable from obstacles, namely the lack of direct and indirect socialization and promotion activities in the community. Many people, especially in Sumedang Regency, are still not aware of this program.